Features of thermal relaxation of polarization in the Nafion membranes with no platinum catalysts - Ногай, А; Кутербеков, К; Ускенбаев, Д; Бекмырза, К; Ногай, А; Кабышев, А (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
In this article the dielectric properties of the polymer membrane Nafion in the membrane-electrode block are studied. The features of the structure of the Nafion, as well as issues relating to the relationship of the structure and dielectric properties in the membranes of the Nafion type are clarified. It is suggested that the catalyst: CoTe/C has a weak effect on the relaxation processes of polarization in the polymer membrane.